Spectrophotometric analysis of the effectiveness of bleaching agents used for non-vital teeth bleaching - Santos, Micheli Reis; de Carvalho, Fabiola Bastos; Cangussu, Maria Cristina Teixeira; Barros, Lays Rocha; Trindade, Renan Ferreira (Journal of Health & Biological Sciences, 2020)
Objectives: This study aimed to compare the efficiency of three different substances used for the bleaching of non-vital teeth. Methods: Forty bovine teeth were divided into five groups: three test groups (sodium perborate + 20% hydrogen peroxide – SPG; 37% carbamide peroxide – CPG; 35% hydrogen peroxide – HPG) and two control groups (CG1 and CG2). Teeth of the test groups were stained artificially with blood and bleached using the in-office and walking bleach techniques. The efficiency of the bleaching agents was evaluated objectively by comparing the color variables L*, a*, and b* measured spectrophotometrically according to the CIELab system. The data were analyzed by ANOVA and the Tukey test, adopting a 5% level of significance. Results: The results showed a reduction in lightness (L*) after staining and an increase after the bleaching sessions. The values of a* and b* increased after staining and decreased after the application of the bleaching substances. Conclusions: All substances used for non-vital tooth bleaching exhibited the same bleaching efficiency. No significant differences in this efficiency were observed between the bleaching techniques at the end of the experiment. However, in-office bleaching provided the same bleaching result as the walking bleach technique within a shorter period. Clinical significance: Given the increasing demand for esthetics, the use of different bleaching techniques and the variety of whitening agents, oral health professionals should offer evidence-based treatment, more efficient and in less time.